ANALISIS GRATIS ONGKIR DAN DISKON PADA KAUM MILENIAL DI MASA PANDEMI COVID 19 (STUDI KASUS PADA E-COMMERCE SHOPEE DI KOTA SANGATTA) - Nuraisyah Yugis Amalia; Riduansah Riduansah; Rizkiawan Rizkiawan (Tinta Nusantara 2018 Vol.1, 2023)
The purpose of this study was to find out the analysis of free shipping and discounts for millennials during the Covid-19 pandemic. The population observed in this study is the Sangatta community, which are millennials, namely people with an age range of 20-40 years who use the formula from Hair and produce 50 respondents. Testing and data processing were carried out using the IBM SPSS Statistics 25 application program. This study uses primary data and secondary data. Primary data was obtained by distributing questionnaires while secondary data was obtained from various sources such as journals and books